Recovery and sleep monitoring in professional ice hockey. Experiences of the German national ice hockey team (mens U20) - Graumann, L. (Current Issues in Sport Science, 2023)
The variable regeneration is still a big unknown, with only a few well researched constants. We still do not know exactly what we can use or recommend in a quality-assured way to optimize or accelerate regeneration. Organizations, associations and clubs have not yet been able to agree on uniform procedures and protocols. This is despite the fact that since 2012, a study led by the of the German Federal Institute for Sport Sciences on this topic has been has been ongoing. You can find the current state of research at any time at www.regman.de.